HISTORY OF COOPERATION OF THE REPUBLIC OF UZBEKISTAN WITH THE COUNTRIES OF CENTRAL ASIA IN THE FIELD OF SCIENCE AND EDUCATION - Abdukxamidov Jalol (Web of Journals Publishing, 2024)
In our article, we talk about the cooperation of the sister Central Asian republics in the field of science and education, reforms, active cooperation and other active socio-political processes.
Keywords: Uzbekistan, the Republic, Central Asia, economy, culture, science, education, cooperation.